2023
DOI: 10.1097/aud.0000000000001436
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Emotional Prosody Identification by School-Age Children With Cochlear Implants and Their Peers With Normal Hearing

Monita Chatterjee,
Shivani Gajre,
Aditya M. Kulkarni
et al.

Abstract: Objectives: Children with cochlear implants (CIs) vary widely in their ability to identify emotions in speech. The causes of this variability are unknown, but this knowledge will be crucial if we are to design improvements in technological or rehabilitative interventions that are effective for individual patients. The objective of this study was to investigate how well factors such as age at implantation, duration of device experience (hearing age), nonverbal cognition, vocabulary, and socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…For voice cue perception, we measured voice discrimination in just-noticeable differences (JNDs) for F0 and VTL (Gaudrain & Başkent, 2015, 2018) (Experiment 3b), and for QoL assessment, we used the NCIQ (Hinderink et al, 2000) (Experiment 3c). We hypothesized that (1) if emotion perception mechanisms are similar across materials, vocal and musical emotion categorization outcomes would be correlated, and arousal and valence dimensions would display similar patterns; (2) acoustic hearing would yield higher vocal and musical emotion categorization scores; (3) voice cue discrimination thresholds and QoL scores would correlate with vocal emotion categorization in line with previous findings (e.g., Chatterjee et al, 2023; Von Eiff et al, 2022), and following reports that vocal and musical emotion perception are similar in CI users (Paquette et al, 2018; Volkova et al, 2013), these individual differences would also be reflected in musical emotion categorization.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…For voice cue perception, we measured voice discrimination in just-noticeable differences (JNDs) for F0 and VTL (Gaudrain & Başkent, 2015, 2018) (Experiment 3b), and for QoL assessment, we used the NCIQ (Hinderink et al, 2000) (Experiment 3c). We hypothesized that (1) if emotion perception mechanisms are similar across materials, vocal and musical emotion categorization outcomes would be correlated, and arousal and valence dimensions would display similar patterns; (2) acoustic hearing would yield higher vocal and musical emotion categorization scores; (3) voice cue discrimination thresholds and QoL scores would correlate with vocal emotion categorization in line with previous findings (e.g., Chatterjee et al, 2023; Von Eiff et al, 2022), and following reports that vocal and musical emotion perception are similar in CI users (Paquette et al, 2018; Volkova et al, 2013), these individual differences would also be reflected in musical emotion categorization.…”
Section: Introductionsupporting
confidence: 59%
“…When tested for the perception of vocal emotions, CI users typically categorize emotions above chance-level, but display categorization accuracy significantly lower than that of normal-hearing (NH) control participants (Chatterjee et al, 2015(Chatterjee et al, , 2023reviewed in Jiam et al, 2017;Lin et al, 2022;Luo et al, 2007;Paquette et al, 2018;Volkova et al, 2013). Emotion categories are sometimes systematically confused with each other, especially when the categories are located on the same end or half-plane of the arousal dimension, for example happy with scared (e.g., Chatterjee et al, 2015;Lin et al, 2022).…”
Section: Perception Of Vocal Emotions With Cochlear Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies related to the use of hearing aids ( Qian et al, 2016 ; Bucholc et al, 2022 ) and cochlear implants ( Mertens et al, 2021 ) have demonstrated that as hearing aids and cochlear implants help to restore auditory perception, the onset of CI is delayed. It is hypothesized that hearing aids ( Reinten et al, 2021 ) and cochlear implants ( Chatterjee et al, 2023 ) improve the “effortful process” of sound discrimination in the daily lives of SNHL patients, and that this change reduces the previous over-allocation of cognitive resources, helping to restore balance in the CL.…”
Section: Hypothesismentioning
confidence: 99%